Analysis of Balanced Nutrition Program Implementation Against Stunting in Toddlers (Unnes Journal of Public Health, 2020)
Nutrition and stunting problems cannot be separated. Unbalanced nutritional intake will result in children experiencing growth and development failure (stunted). The purpose of this study was to evaluate the process of implementing a balanced nutrition program in overcoming the problem of stunting carried out by health workers in the working area of ​​Bantilang Public Health Center. The research design used descriptive qualitative. The sample amounted to 15 informants. Sampling used a purposive sampling technique. Data analysis using the Collaizi (1978) method. This study produced a number of themes, namely: (1). Balanced Nutrition Program implementation was running less than optimal; (2). Barriers to the implementation of the Balanced Nutrition Program; (3). Efforts to overcome barriers to the Balanced Nutrition Program at the Public Health Center in Bantilang. The Balanced Nutrition Program in the work area of ​​the Bantilang Public Health Center has been implemented, but it has not yet run optimally due to several obstacles including limited community participation and local government. So it is necessary to monitor and evaluate the implementation of the Balanced Nutrition Program by the East Luwu District Health Office.